Novel Copy Denture Technique—A Practical Approach for Duplicating Existing Dentures - Khan, Mehwish; Kazmi, Syed Murtaza Raza; Quraeshi, Sameer; wazir, Shah (European Journal of General Dentistry, 2022)
Provision of copy dentures to complete denture patients is often needed in clinical practice. Several edentulous patients want an additional set of dentures to avoid being without them in case the existing ones are broken or lost, whereas some patients have adapted to their old dentures so much that they do not want them to be replaced by a completely new prosthesis. This article presents a technique for the fabrication of a copy denture that allows duplicate dentures to be processed in heat-cure acrylic resin in two clinical visits, without leaving the dentures at dental office.
Keywords: copy denture; duplicate denture; denture copy technique